The Relationship Of Knowledge, Perception Of Husband Support With A Selection Of Iud Contraception Equipment In The Work Area Of Pauh - Fitri Khoiriyah; Yusmalia Hidayati; Dita Anggriani Lubis; Dilma'aarij Agustia; Ria Fazelita Br Gultom; Wiwiek Elsada Nainggolan (LPPM Universitas PGRI Sumatera Barat, 2024)
One of the family planning program goals is to improve the healthy of mothers and children, to embody a happy and prosperous family. One way to decrease the population growth is to increase the use of MKJP, especially the IUD. The low usage of IUDs in Indonesia causes uncontrolled population growth. The same problem happened in West Sumatra. The purpose of this research was to determine the relationship of knowledge, perception of husband's support with the selection of IUD contraceptives. This research was a cross-sectional comparative. The populations in this research were all women of childbearing age (WUS). The samples of this research were 49 IUD users and 149 non-IUD users. The instruments were a questionnaire. The bivariate analysis used Chi-Squere. The results of the univariate study found that 123 people (62,1%) had low knowledge, 125 WUS (63,1%) received support from their husbands to use contraception. The results of this study found that there was a significant relationship between knowledge and the selection of IUD contraceptives (p = 0.001). There was a significant relationship between the perception of the husband's support and the selection of IUD contraceptives (p = 0.001). This study concludes that there is a relationship of knowledge and perception of the husband's support for choosing IUD contraceptives.